2011
DOI: 10.1007/s11745-011-3528-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Fatty Acid Content and Composition by Exposure to Dyslipidemic Serum in Vitro

Abstract: Macrophages in arterial walls accumulate lipids leading to the development of atherosclerotic plaques. However, mechanisms underlying macrophage lipid accumulation and foam cell formation are often studied without accounting for risk factors such as dyslipidemia. We investigated the effect of varying concentrations of triglyceride (TG) within physiological range on macrophage fatty acid (FA) accumulation and expression of cholesterol efflux proteins. Human monocytes were cultured in media supplemented with 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The author suggests that hypertriglyceridemia may increase the risk of CAD via direct actions on macrophages favoring foam cell formation, thus leading to the development of atherosclerotic plaque. 44 Changes in ABCG1 DNA methylation might mediate the development of atherosclerotic plaques in response to high triglyceride levels. Thus, with this study, we found hints for a new perspective on the molecular background of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The author suggests that hypertriglyceridemia may increase the risk of CAD via direct actions on macrophages favoring foam cell formation, thus leading to the development of atherosclerotic plaque. 44 Changes in ABCG1 DNA methylation might mediate the development of atherosclerotic plaques in response to high triglyceride levels. Thus, with this study, we found hints for a new perspective on the molecular background of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 Additionally, recent studies indicate that macrophages of atherosclerotic plaques accumulate FFAs; 1315 however, the molecular consequences of intracellular FFAs remain relatively unknown. Increased partitioning of FFA to TG (via DGAT-1 overexpression) protects macrophages from FFA-induced inflammation, 31 suggesting that accumulation of FFAs, rather than TG, in these immune cells may be responsible for inflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, treatment of human macrophages with dyslipidemic serum increases intracellular FFA concentrations. 14, 15 Therefore, determining the consequences of intracellular FFA accumulation within macrophages is of critical importance. Our lab has previously shown that accumulation of the saturated FFA, stearic acid, in macrophages results in apoptotic cell death; 16 however, the mechanism of lipotoxicity remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages in particular implicate a series of converging events that sequentially re-define in repetitive form the dynamics of atherogenesis. Dyslipidemmia increases lipid content in foam cells found in atherosclerotic plaques (Wong et al, 2011).…”
Section: System Pathways Of Injurymentioning
confidence: 99%